86.2k views
5 votes
What ia the solution to the original equation

What ia the solution to the original equation-example-1
User Kgx
by
5.0k points

1 Answer

4 votes

8(3x−7)=−6(x+7)+4

(8)(3x)+(8)(−7)=(−6)(x)+(−6)(7)+4(Distribute)

24x+−56=−6x+−42+4

24x−56=(−6x)+(−42+4)(Combine Like Terms)

24x−56=−6x+−38

24x−56=−6x−38

Step 2: Add 6x to both sides.

24x−56+6x=−6x−38+6x

30x−56=−38

Step 3: Add 56 to both sides.

30x−56+56=−38+56

30x=18

Step 4: Divide both sides by 30.

30x /30= 18/30

x= 3/5

User Timbillstrom
by
5.1k points